Civil society strategy: a policy review. (1st July 2019) - Bennett, Ellen; Coule, Tracey; Damm, Chris; Dayson, Chris; Dean, Jon; Macmillan, Rob
Abstract : In August 2018, the UK government published its Civil society strategy for England, aiming to establish a policy agenda for creating social value. This paper reviews the strategy, critically assessing its contribution to the creation of social value, the civil society‐state relationship, public sector commissioning and youth participation. By concluding with an analysis of the strategy's language, we argue that there are risks in the strategy's narrative positioning of voluntary action and wider civil society.